Analisis Sistem Pengendalian Internal Atas Persediaan Barang Dagang Pada PD. Indah Permai Group - Somendari, Ni Nengah Wulan; Suryantara, Adhitya Bayu (Jurnal Riset Mahasiswa Akuntansi, 2025)
This study aims to analyze the internal system over merchandise inventory at PD. Indah Permai Group using the COSO (Committee of Sponsoring Organizations) framework. The research employed a qualitative descriptive approach with data collected thorugh observation, interviews, questionnaires, and documentation. The assessment focused on the five main components of the COSO framework. The result show that the internal control system at PD. Indah Permai Group is categorized as highly effective, with an overall score of 89,3%. However, some weaknesses were identified, such as the absence of an independent audit committee and the end to improve information systems and interdepartmental coordination. Strengthening these aspects is expected to enhance the sustainability and effectiveness of internal control in supporting operational efficiency and achieving organizational goals.